Currency rate its evolution from 1960 to 2020 and the exchange policies applied in Costa Rica - Carvajal-Pérez, Ana Lorena (2021)
This work is the result of the analysis and evaluation of what human talent management represents in the current work environment. The main goal is to set a new way of viewing management, starting from a bibliographic review of human resources management, and its evolution through time, highlighting the importance of its transformation, going through organizational progress, and concluding that a change in human talent management its required, in order to increase the strategical support, it can bring to organizational goals achievement.